Relationship between Foot Length Measurements and Body Height: A Prospective Regional Study among Adolescents in Central Region of Kosovo - Fitim Arif; Jovan Gardasevic; Bojan Masanovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The research purpose is to examine standing height in association with foot length in both Kosovan genders in the Central Region, as an alternative to estimating standing height. A 193 individuals (100 male and 93 female) were examined. The anthropometric measurements were taken according to the protocol of ISAK. Body height and foot length relationships were determined using simple correlation coeffi cients at a ninety-fi ve percent confi dence interval. A comparison of means of standing height and foot length between genders was performed using a t-test. After that a linear regression analysis were carried out to examine extent to which foot length can reliably predict standing height. Results displayed that Central Kosovan male are 180.32±5.88 cm tall and have a foot length of 26.41±1.09 cm, while female are 166.77±4.72 cm tall with a foot length of 23.61±0.92 cm. The results have shown that both genders made Central-Kosovans a tall group, taller that general Kosovan population. Moreover, the foot length reliably predicts standing height in both genders; but, not reliably enough as arm span. This study also confi rms the necessity for developing separate height models for each region in Kosovo as the results from Central-Kosovans don't correspond to the general values.